Biochemical and Microstructural Profile of the Thyroid Gland from Lambs Raised on Experimental Diets - Giro Tatiana M.; Kulikovsky Andrey V.; Knyazeva Alexandra S.; Domnitsky Ivan Yu.; Giro Anna V. (Техника и технология пищевых производств)
Introduction. The present research featured biochemical and microstructural features of thyroid glands obtained from lambs raised on various feeds enriched with essential elements. The article focuses on iodine as the most important physiologically active microelement. Iodine participates in the synthesis of thyroid hormones, namely thyroxine and triiodothyronine, which are known to regulate metabolic processes. Iodine deficiency may impair reproductive function and cause such diseases as endemic goiter. Study objects and methods. The study involved thyroid glands from lambs of the Edilbaev breed aged seven months. The lambs were divided into four experimental groups, ten animals in each. The lambs received several feed additives. Ioddar-Zn and DAFS-25 had a balanced protein and carbohydrate content, while the mineral feed of Coretron brand contained such trace elements and minerals as iodine, selenium, and silicon. Results and discussion. The experiment made it possible to describe the microstructural profile of the thyroid glands extracted from seven-month-old lambs raised on feeds enriched with iodine and selenium. Ioddar-Zn and DAFS-25 did not harm the structure of the thyroid tissue, while causing its functional activation in some cases. The morphological parameters of the thyroid glands indicated some breed differences. The iodine concentration in the thyroid glands obtained from the experimental animals was five or six times higher than that in the control group. The content of mono- and diiodotyrosine depended on the accumulation profile of organic iodine. Conclusion. Diets enforced with DAFS-25, Ioddar-Zn, silicon, and a protein-carbohydrate complex produced no negative effect on the structure of the thyroid tissue. It fact, the diet increased the organic iodine content in the thyroid glands in the form of iodotyrosines. The gland structure revealed some cubic epithelium or follicular cells. The mass spectrometric studies confirmed the presence of covalently bound iodine in the form of mono- and diiodotyrosine. Thus, the abovementioned feed additives can be recommended for industrial use.